Pengaturan Keberlakuan Surat Izin Usaha Perdagangan Bagi Pelaku Usaha E-Commerce - Suta, Made Ary; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p1, 2022)
The purpose of this study is to examine the regulation of Trading Business Licences towards e-commerce business actors and the legal consequences that arise when e-commerce business actors do not have a Trading Business Licenses. The approach method used in this article is normative legal research wuth statute and conceptual approaches. The results show that e-commerce business actors are required to have a Trading Business Licenses in the form of SIUPMSE as stipulated in Government Regulation Number 80 of 2019 and Minister of Trade Regulation Number 50 of 2020 while legal consequences that arise for e-commerce business actors with no SIUPMSE will be subject to criminal sanctions as regulated in Article 46 Section 34 Chapter III of the Job Creation Law which amends the provisions of Article 106 of the Law on Trade in the form of imprisonment for a maximum of 4 (four) years or a fine of a maximum of Rp. 10,000,000,000.00 (ten billion rupiah) and administrative sanctions based on Article 80 paragraph (2) of Government Regulation Number 80 of 2019 and hereinafter specifically regulated in Article 44 paragraph (2) of the Regulation of the Minister of Trade Number 50 of 2020.